The Parasitization Rate of Larva-Pupal Parasitoid Phobetes nigriceps (Gravenhorst) (Hymenoptera: Ichneumonidae) of Almond Leaf Bee Cimbex quadrimaculata (O. F. Muller) (Hymenoptera: Cimbicidae) in the Diyarbakir and Elazig Provinces - Ozgen, Inanc; Riedel, Matthias (Springer, 2023)
The Almond leaf bee Cimbex quadrimaculata (Muller 1766) (Hymenoptera: Cimbicidae) is one of the important pests of almond fields. In order to determine larval parasitoids of this pest, studies were carried out in Keban district of Elazig province and Egil district of Diyarbakir province, Turkey. In 2019-2020, 100 larvae taken into culture in both locations were ensured to pupate and percent parasitization rates were determined in larval parasitoids emerging from pupae in 2020-2021. Parasitoid escapes were determined by the controls made twice a week starting from January in the years of the study. Obtained parasitoids were determined as Phobetes nigriceps (Gravenhorst 1829) (Hymenoptera: Ichneumonidae, Ctenopelmatinae) as a second record of this parasitoid from Turkey. The width of the hatching hole of the species and the percentage of parasitism in two different locations were determined: The width of the exit holes varied from 8.12 to 9.14 mm. The parasitization rates were 13% in 2020 and 11% in 2021 in the orchard in the Egil location, 8% in 2020 and 6% in 2021 in the Keban location.
Keywords: Almond; Cimbex quadrimaculata; Phobetes nigriceps; Parasitization rate; Turkey